2020
DOI: 10.12669/pjms.36.5.1916
|View full text |Cite
|
Sign up to set email alerts
|

Behcet’s Disease: Pakistani Experience

Abstract: Objective: To analyze the clinical manifestation of patients with Behcet’s disease, and performance of different classification criteria of Behcet’s disease in our population. Methods: It was a retrospective analysis of all Behcet’s disease patients attending Department of Rheumatology at Fatima Memorial Hospital, Lahore, Pakistan from April 2019 to July 2019. We performed a comprehensive clinical evaluation of patients with Behcet’s disease, with focus on patients’ age, gender and different clinical man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A study on 20 patients with BD in Pakistan showed no significant difference between men and women in terms of clinical manifestations, 1 which may be due to the limited sample size. However, significant associations have been reported between gender and clinical manifestations in studies with high sample size.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study on 20 patients with BD in Pakistan showed no significant difference between men and women in terms of clinical manifestations, 1 which may be due to the limited sample size. However, significant associations have been reported between gender and clinical manifestations in studies with high sample size.…”
Section: Discussionmentioning
confidence: 97%
“…Clinically, BD presents with oral and genital aphthous ulcers, skin lesions, ocular, articular, neural, and gastrointestinal manifestations. 1 Regarding geographical distribution, BD has a higher prevalence in Mediterranean countries, Far East, and the Middle East, while being less prevalent in America, Oceania, and sub-Saharan Africa. 2 Current evidence shows that the highest prevalence of BD belongs to Turkey (20 to 420 patients per 100,000 population) and Iran (80 to 100 patients per 100,000 population).…”
Section: Introductionmentioning
confidence: 99%
“…The common clinical feature of patients with Bechet disease is mucocutaneous ulcers, but it can also involve other systems, such as gastrointestinal, neurological, and vascular [ 13 ]. The oral and ocular symptoms of the disease are the most common manifestation, with a frequency of more than 80% [ 14 ].…”
Section: Discussionmentioning
confidence: 99%